2017
DOI: 10.1186/s12882-017-0535-4
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal nephromegaly and propionic acidemia: a case report

Abstract: BackgroundPropionic acidemia (PA) is a rare but severe recessive autosomal disease, presenting with non specific signs in the first years of life. Prenatal diagnosis is invasive (amniocentesis) and limited to suspect cases. No screening test has been described, in particular no correlations between prenatal sonography and PA have been documented so far.Case presentationWe report the case of a boy with fetal bilateral nephromegaly and hyperechogenic kidneys, along with neonatal acute kidney injury; no etiology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…A previous study has reported a previously healthy adolescent individual suffering from isolated dilated cardiomyopathy without history of metabolic decompensation also had reduced PCC enzyme activity and pathogenic variants in PCCB gene [108]. Recently, a male neonate born with nephromegaly and acute kidney injury with unknown cause was later found to have PA following a metabolic decompensation episode at the age of three months [109]. It remains unclear whether the congenital renal anomalies are related to this individual’s PA diagnosis.…”
Section: Reviewmentioning
confidence: 99%
“…A previous study has reported a previously healthy adolescent individual suffering from isolated dilated cardiomyopathy without history of metabolic decompensation also had reduced PCC enzyme activity and pathogenic variants in PCCB gene [108]. Recently, a male neonate born with nephromegaly and acute kidney injury with unknown cause was later found to have PA following a metabolic decompensation episode at the age of three months [109]. It remains unclear whether the congenital renal anomalies are related to this individual’s PA diagnosis.…”
Section: Reviewmentioning
confidence: 99%
“…A pathogenic PCCB gene (mutation) is related to cardiomyopathy in clinical reports (Bernheim et al. 2017 ). The relationship between the PCCB expression level and cardiovascular defects remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Congenital urinary abnormalities are often associated with the kidney anomalies, and there is a wide range of malformations resulting from disorders in the normal development process [9].…”
Section: Classificationmentioning
confidence: 99%
“…e. Unilateral asymmetric fusions. There is a single kidney mass with a crossed ectopic kidney, known as 'the sigmoid kidney', usually located in the pelvis [7][8][9][10].…”
Section: Classificationmentioning
confidence: 99%
See 1 more Smart Citation